How do clinical genetics consent forms address the familial approach to confidentiality and incidental findings? A mixed-methods study - Dheensa, S; Crawford, G; Salter, C; Parker, M; Fenwick, A; Lucassen, A (Springer Netherlands, 2017)
Genetic test results can be relevant to patients and their relatives. Questions thus arise around whether clinicians regard genetic information as confidential to individuals or to families, and about how they broach this and other issues, including the potential for incidental findings, in consent (forms) for genetic testing. We conducted a content analysis of UK-wide genetic testing consent forms and interviewed 128 clinicians/laboratory scientists. We found that almost all genetic services offered patients multiple, sometimes unworkable, choices on forms, including an option to veto the use of familial genetic information to benefit relatives. Participants worried that documented choices were overriding professional judgement and cautioned against any future forms dictating practice around incidental findings. We conclude that 'tick-box' forms, which do little to enhance autonomy, are masking valid consent processes in clinical practice. As genome-wide testing becomes commonplace, we must re-consider consent processes, so that they protects patients'-and relatives'-interests.